2008
DOI: 10.1080/10286020701782692
|View full text |Cite
|
Sign up to set email alerts
|

Two new lignan glycosides fromTrachelospermum lucidum(D. Don) Schum

Abstract: Two new triterpenoid saponins (1, 2) and a known sapogenin (3) were isolated from the dried carpophore of Xanthoceras sorbifolia Bunge. (Sapindaceae), and their structures were established as 3-O-beta-d-glucopyranosyl, 28-O-[alpha-l-rhamnosyl (1 --> 2)]-beta-d-glucopyranosyl 16-deoxybarrin-gtogenol C (1), 3-O-[beta-d-glucopyranosyl(1 --> 6)] 3'-angeloyl)-beta-d-glucopyranosyl, 28-O-[alpha-l-rhamnosyl(1 --> 2)]-beta-d-glucopyranosyl 16-deoxybarringtogenol C (2), 16-deoxybarringtogenol C (3), by spectral and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The absolute configurations of C-8 and C-8′ were established as 8 S ,8′ R by the correlation of H-7/8′ in the ROESY spectrum and the negative Cotton effects at 243 and 282 nm in the CD spectrum. However, in the 1 H NMR spectrum of 11a (the aglycone) (Figure S84, Supporting Information), which was obtained by hydrolysis of 11 , the coupling constant of H-7 ( J 7,8 = 8.5 Hz) suggested that the relative configuration between C-7 and C-8 was threo instead of the erythro configuration in 9 . Thus, the 7 R configuration was determined and the structure of 11 was characterized as Figure and named (7 R ,8 S ,8′ R )-4,7-dihydroxy-3,3′,4′-trimethoxyl-9-oxo dibenzylbutyrolactone lignan-4- O -β- d -glucopyranoside.…”
Section: Resultsmentioning
confidence: 99%
“…The absolute configurations of C-8 and C-8′ were established as 8 S ,8′ R by the correlation of H-7/8′ in the ROESY spectrum and the negative Cotton effects at 243 and 282 nm in the CD spectrum. However, in the 1 H NMR spectrum of 11a (the aglycone) (Figure S84, Supporting Information), which was obtained by hydrolysis of 11 , the coupling constant of H-7 ( J 7,8 = 8.5 Hz) suggested that the relative configuration between C-7 and C-8 was threo instead of the erythro configuration in 9 . Thus, the 7 R configuration was determined and the structure of 11 was characterized as Figure and named (7 R ,8 S ,8′ R )-4,7-dihydroxy-3,3′,4′-trimethoxyl-9-oxo dibenzylbutyrolactone lignan-4- O -β- d -glucopyranoside.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, T. liukiuense , T. axillare , T. lucidum, T. fragrans , T. difforme and T. gracilipes are also used for phytochemistry research. Up to now, over 130 compounds have been isolated from the genus Trachelospermum( Table 1 ) , among which lignans (23.9%) [2,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20], triterpenoids (35.5%) [2,21,22,23,24,25,26,27,28,29,30,31], flavonoids (21.7%) [13,21,32,33,34,35,36,37,38,39,40,41,42] are the major categories. All the compounds we summarize are compiled in Table 1.…”
Section: Phytochemistrymentioning
confidence: 99%
“…The dioxygenation patterns may involve the 3,4-, 2,4-, 2,5-, and 2,6-positions but seldomly the 3,5-positions. However, certain “new” naturally occurring compounds with 3,5-dioxygenated aromatic rings have been reported in recent years (Figure ), including flavanones, dihydroflavonols, flavans, isoflavones, tetrahydrofuran lignans, furofuran lignans, and other compounds.…”
mentioning
confidence: 99%
“…However, in 1998, Anthoni et al demonstrated that the substituted pattern of the B-ring was incorrect by synthesizing racemic 3′,5,5′,7-tetrahydroxyflavanone using 2-hydroxy-4,6-diisopropyloxyacetophenone and 3,5-diisopropyloxybenzaldehyde. Since then, at least 27 “new” natural compounds with 3,5-dioxygenated aromatic rings have been reported. , These articles were cited by many researchers who ignored the incorrect elucidation of the 3,5-dioxygenated aromatic ring. These findings inspired us to investigate this problem more thoroughly and to clarify the difference between 3,4- and 3,5-dioxygenated aromatic rings using NMR experiments.…”
mentioning
confidence: 99%